Construções com régua e compasso envolvendo lugares geométricos: uma proposta dinâmica aliada a teoria de registros de representação semiótica - Lied, Roberta (2016)
The focus of this thesis is on the study of geometric places, and it has as objective research: "to investigate the mobilization of registers of semiotic representation through educational activities involving geometric places in two learning environments: when using paper, pencil, ruler and compass and when using GeoGebra software." Therefore, under the light of this research perspective, a series of activities were designed and implemented with the undergraduate students in Mathematics at the Federal University of Santa Maria. The theoretical foundation is based on Raymond Duval s Registers of Semiotics Representation Theory. It should be noted that this theory of learning has an extensive reference on the visualization process and, thus, has relevance in the teaching and learning of geometry. As a qualitative research, the analysis of the results occurred from the perceptions and procedures developed by the students during the development of the sequence of activities. In this sense, we analyzed which registers of semiotics representation were used by students in the two proposed learning environments. From this analysis, it was found that the different seizures and ways of seeing a geometrical figure distinguished by Duval were contemplated. In addition to that, the use of GeoGebra software favored the visual aspect of mathematical objects, with emphasis on figural register.